2010
DOI: 10.1128/aem.00831-10
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Factor, Rather than Elevated CO 2 , Controls the Soil Bacterial Community in a Temperate Forest Ecosystem

Abstract: The global atmospheric carbon dioxide (CO 2 ) concentration is expected to increase continuously over the next century. However, little is known about the responses of soil bacterial communities to elevated CO 2 in terrestrial ecosystems. This study aimed to partition the relative influences of CO 2 , nitrogen (N), and the spatial factor (different sampling plots) on soil bacterial communities at the free-air CO 2 enrichment research site in Duke Forest, North Carolina, by two independent techniques: an entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 82 publications
(108 reference statements)
2
19
0
Order By: Relevance
“…Responses of AOB and AOA community structure to elevated CO 2 and N fertilization CCA results revealed that soil niche properties significantly influenced the amoA genotype distribution of AOB and AOA rather than elevated CO 2 (p > 0.1) or N fertilization (p > 0.1). Previous study of this site already showed that the spatial difference rather than elevated CO 2 shaped the distribution of bacterial community (Ge et al, 2010). A study on the response of AOB and AOA in the rhizosphere of maize and soybean to elevated CO 2 showed no significant difference among treatments based on unweighted PCA of the amoA gene sequences (Nelson et al, 2010).…”
Section: Responses Of Aob and Aoa Abundance To Elevated Co 2 And N Fementioning
confidence: 79%
See 2 more Smart Citations
“…Responses of AOB and AOA community structure to elevated CO 2 and N fertilization CCA results revealed that soil niche properties significantly influenced the amoA genotype distribution of AOB and AOA rather than elevated CO 2 (p > 0.1) or N fertilization (p > 0.1). Previous study of this site already showed that the spatial difference rather than elevated CO 2 shaped the distribution of bacterial community (Ge et al, 2010). A study on the response of AOB and AOA in the rhizosphere of maize and soybean to elevated CO 2 showed no significant difference among treatments based on unweighted PCA of the amoA gene sequences (Nelson et al, 2010).…”
Section: Responses Of Aob and Aoa Abundance To Elevated Co 2 And N Fementioning
confidence: 79%
“…35% mostly since the beginning of industrialization. Atmospheric CO 2 enrichment has been shown to significantly influence the structure and function of terrestrial ecosystems (Rosenzweig et al, 2007), adding to or interacting with the spatial and temporal effects of environmental variables (Ge et al, 2010). Soil microorganisms, encompassing the greatest diversity in terrestrial ecosystems, are the key drivers in almost all global biogeochemical cycles (Fuhrman, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding effects of global change on soil microbial communities has focussed largely on community structure associated with a single environmental factor such as elevated [CO 2 ], nitrogen (N) deposition, and warming. However, in these experiments, effects of associated global change factors potentially varied with treatment length and type, ecosystem and soil type, and other environmental conditions (Montealegre et al 2000;Frey et al 2008;Xu et al 2009;Ge et al 2010). Given that soil microorganisms are the key drivers of soil nutrient cycling (e.g., Falkowski et al 2008), their roles in mediating climate change and ecosystem functioning are not well understood (Balser et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The soil sampling approach most widely used in CO 2 studies is the bulked soil method providing a single soil sample per FACE ring or OTC; examples where bacterial abundance has been measured are given in Table 1 and there are further examples where the object was to study bacterial community structure and diversity [42] [16]. The results for bacterial abundance in eCO 2 field experiments shows a consistent reduction in abundance with eCO 2 ; the only exception in the experiments listed being a slight and non-significant response in one set of measurements in this paper (Figure 3(B)).…”
Section: Effect Of Different Methods Of Soil Sampling and Dna Extractmentioning
confidence: 99%